Revisiting the Revisited: An Alternative Test of the Monopolistic Competition Model of International Trade - Kamata, Isao (My University, 2010)
This paper proposes an alternative test of the monopolistic competition model of international trade that has an implication for the relationship between the volume of trade and similarity among trading countries in the sizes of their economies. As the model predicts, the result shows that for industrial countries, the positive correlation between the volume of trade and the similarity of economic size among countries is more significant in the sectors characterized by product differentiation. However, for developing countries, the predicted relationship is more pronounced in the non-differentiated sectors, counter to what the model suggests.